2003
DOI: 10.1038/sj.npp.1300367
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of M1/M4 Muscarinic Receptors in the Anterior Cingulate Cortex in Schizophrenia, Bipolar Disorder, and Major Depression Disorder

Abstract: Abnormal cholinergic neurotransmission has been suggested to occur in psychiatric illness. Therefore, this study investigated cholinergic muscarinic receptors in the anterior cingulate cortex (ACC) of schizophrenia, bipolar disorder and major depression disorder (n ¼ 15 per group). We used quantitative autoradiography to measure [ 3 H]pirenzepine binding to M1 and M4 receptors. Brain tissue was obtained from the Stanley Foundation Neuropathology Consortium. [ 3 H]pirenzepine binding was higher in superficial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(39 citation statements)
references
References 29 publications
2
35
0
2
Order By: Relevance
“…The M 1 receptor subtype is the most abundant of the muscarinic receptors in the cortex and hippocampus (Levey et al, 1991;Wei et al, 1994), brain regions crucial to cognitive function. Decreased M 1 receptor binding has been reported in postmortem studies of the prefrontal cortex, hippocampus, and striatum from patients with schizophrenia (Dean et al, 1996;Crook et al, 2000Crook et al, , 2001Katerina et al, 2004); and decreased M 1 -receptor cDNA levels in the frontal cortex have also been reported (Mancama et al, 2003). This has contributed to the suggestion that enhancement of central cholinergic neurotransmission by M 1 agonists might be useful to treat the cognitive impairments of schizophrenia (Sur et al, 2003;Weiner et al, 2004).…”
Section: Introductionmentioning
confidence: 81%
“…The M 1 receptor subtype is the most abundant of the muscarinic receptors in the cortex and hippocampus (Levey et al, 1991;Wei et al, 1994), brain regions crucial to cognitive function. Decreased M 1 receptor binding has been reported in postmortem studies of the prefrontal cortex, hippocampus, and striatum from patients with schizophrenia (Dean et al, 1996;Crook et al, 2000Crook et al, , 2001Katerina et al, 2004); and decreased M 1 -receptor cDNA levels in the frontal cortex have also been reported (Mancama et al, 2003). This has contributed to the suggestion that enhancement of central cholinergic neurotransmission by M 1 agonists might be useful to treat the cognitive impairments of schizophrenia (Sur et al, 2003;Weiner et al, 2004).…”
Section: Introductionmentioning
confidence: 81%
“…92 However, this group did report a significant reduction in the levels of M 1 and M 4 muscarinic receptors in the anterior cingulate cortex in schizophrenia. 93 These changes were shown to have some disease-specificity as the density of M 1 and M 4 muscarinic receptors was not altered in the same CNS region from subjects with bipolar disorder or major depression. 93 In the superior temporal gyrus, another relevant brain region for schizophrenia, the density of M 1 and M 4 muscarinic receptors (using pirenzepine) was significantly decreased in schizophrenia.…”
Section: Post-mortem Cns Studiesmentioning
confidence: 90%
“…93 These changes were shown to have some disease-specificity as the density of M 1 and M 4 muscarinic receptors was not altered in the same CNS region from subjects with bipolar disorder or major depression. 93 In the superior temporal gyrus, another relevant brain region for schizophrenia, the density of M 1 and M 4 muscarinic receptors (using pirenzepine) was significantly decreased in schizophrenia. M 2 and M 4 muscarinic receptor levels in the same brain region (using AF-DX 384) showed a decrease that failed to reach significance.…”
Section: Post-mortem Cns Studiesmentioning
confidence: 90%
“…Nevertheless, postmortem, clinical imaging, and genetic approaches have further implicated mAChR expression and function in the underlying pathophysiology of schizophrenia. Several postmortem [ 3 H]pirenzepine-binding studies have demonstrated decreased levels of M 1 /M 4 mAChRs in specific brain regions of schizophrenic patients, including the prefrontal and anterior cingulate cortices, superior temporal gyrus, hippocampus, and dorsal striatum (Dean et al, 1996(Dean et al, , 2002Crook et al, 1999Crook et al, , 2000Crook et al, , 2001Katerina et al, 2004;Deng and Huang, 2005). These changes in mAChR expression appear to be specific to schizophrenia, as similar decreases were not observed in patients with bipolar disorder or major depression (Zavitsanou et al, 2004).…”
Section: Role Of Muscarinic Receptor Subtypes In Schizophreniamentioning
confidence: 99%